Masa de mesones y bariones: un tratamiento unificado - Paredes Torres, Gustavo (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
This work shows how the masses of hadrons composed of quarks u, d, s, c and b are calculated in a model called Contact Interaction (CI). The mathematical basis for this analysis is implemented through the use of CI in the Schwinger-Dyson equations (SDE) and the Bethe-Salpeter (BS) equations for mesons and diquarks. Later this model was implemented in the Faddeev equation to calculate the mass of the baryons using a quark-diquark approximation. This study requires the calculation of the masses of the diquark correlations, which are inferred by solving the BS equations for the corresponding mesons. Diquarks are quark-quark correlations used in a novel way. Extensive theoretical and experimental studies of baryons containing c and b quarks have been a source of vigorous research in recent years. Currently there are ongoing experimental programs active in various laboratories (LHCb, BELLE, PANDA, JLAB) to study heavy hadrons, their masses, lifetimes and weak decays. Our results are in agreement with existing experimental data whenever a comparison can be made, as well as with the predictions of other reasonable theoretical approaches.

Este trabajo muestra cómo las masas de hadrones compuestos por quarks u, d, s, c y b se calculan en un modelo llamado Interacción de contacto (CI). La base matemática para este análisis se implementa mediante el uso de CI en las ecuaciones de Schwinger-Dyson (SDE) y las ecuaciones de Bethe- Salpeter (BS) para mesones y diquarks. Posteriormente este modelo se implementó en la ecuación de Faddeev para calcular la masa de los bariones utilizando una aproximación quark-diquark. Este estudio requiere el cálculo de las masas de las correlaciones de diquark, que se infieren resolviendo las ecuaciones de BS para los mesones correspondientes. Los diquarks son correlaciones quark-quark que se utilizan de forma novedosa. Los extensos estudios teóricos y experimentales de bariones que contienen quarks c y b han sido una fuente de investigación vigorosa en los últimos años. Actualmente existen programas experimentales activos en varios laboratorios (LHCb, BELLE, PANDA, JLAB) para estudiar hadrones pesados, sus masas, tiempos de vida y desintegraciones débiles. Nuestros resultados están de acuerdo con los datos experimentales existentes siempre que se pueda hacer una comparación, así como con las predicciones de otros enfoques teóricos razonables.
Instituto de Física y Matemáticas. Maestría en Ciencias en el Área de Física
Keywords: info:eu-repo/classification/cti/1; IFM-M-2021-0152; Quark; Mesón; Diquark; Faddeev; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3991